Research Studies on the Thrust of Special-Shaped Full-Sectional Cutterheads of Quasirectangular Shield - Yaohong Zhu; Jiawei Wang; Bayang Zhang; Xuqing Zhang; Jue Zhu (Advances in Civil Engineering)
Thrust of shield cutters is the major parameter of tunnel construction and an important index for shield machine design. The thrust bearing resistance of a shield machine has a significant impact on its construction efficiency and safe operation. The use of quasirectangular shield not only can increase the space utilization rate but also avoid the deformation of the back soil when compared with a conventional circular or rectangular shield. In this paper, structural analysis of quasirectangular shield cutterhead is carried out and a corresponding mathematical thrust model is developed. Both the stress and displacement distributions of cutterhead are calculated. It is found that the stress value in most regions of the cutterhead is between 5 MPa and 45 MPa. The maximum stress is 208.44 MPa, which is at the middle part of the rib and is below the yield limit. The maximum deformation is found in the center area of the chest plate, the value of which is also within the design requirement. In addition, a monitoring method suitable for quasirectangular shield is proposed. The appropriateness and reliability of the proposed monitoring method are demonstrated by the comparison between the numerical simulation and monitoring method.